An evaluation of the market-timing and security-selection performance of mutual funds: The case of Malaysia - Low, Soo Wah; Ghazali, Noor Azlan (Universiti Utara Malaysia, 2005)
In this article, we examine market-timing and security-selection performance of a sample of Malaysian mutual funds. We used Jensen’s (1968; 1969) model to test for the overall fund performance and employed the model developed by Merton (1981) and Henriksson and Merton (1981) to highlight the separate contributions of market-timing and security-selection performance to the overall fund’s return. Consistent with most previous research, we find evidence that the funds provide investors with overall negative return performance. Since such performance evaluation ignored the existence of timing activities among fund managers, it attributed the overall negative performance exclusively to the manager’s security-selection efforts. When we model timing and selectivity simultaneously using the Henriksson and Merton’s (1981) model, we find evidence of negative market-timing performance by fund managers. Perhaps more importantly, our results suggest that after accounting for the manager’s market-timing ability, the manager’s security-selection ability no longer contributes significantly to the overall fund performance. That is, the overall negative return performance of the fund is driven by the poor timing ability of the fund manager. The evidence presented highlights the importance of considering both the market-timing and the security-selection abilities of the fund manager when evaluating the performance of mutual funds to avoid erroneous conclusions regarding the fund performance.